2021
DOI: 10.1039/d1tb00779c
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the synthesis and applications of graphene–polypeptide nanocomposites

Abstract: The combination of peptides and graphene-derived materials provides a new way to prepare graphene-based nanocomposites with unique structures, properties, and functions. The modification of graphene with different polypeptides not only...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…The advantages of peptide-conjugated nanoparticles in the in vivo applications combine the benefits from peptide properties, i.e., modular structure, established geometry, facile derivatization, and tailoring to specific targets, with the nanoparticle features, bringing membrane permeability, increased half-life, and bioavailability from a broad range of materials used as carriers, from gold nanoparticles to graphene [201]. This relatively new area of research leaves some important questions still open, mostly concerning long-term toxicity, biodistribution, and environmental impact.…”
Section: Discussion: Peptide Biosensors-advantages and Applicationsmentioning
confidence: 99%
“…The advantages of peptide-conjugated nanoparticles in the in vivo applications combine the benefits from peptide properties, i.e., modular structure, established geometry, facile derivatization, and tailoring to specific targets, with the nanoparticle features, bringing membrane permeability, increased half-life, and bioavailability from a broad range of materials used as carriers, from gold nanoparticles to graphene [201]. This relatively new area of research leaves some important questions still open, mostly concerning long-term toxicity, biodistribution, and environmental impact.…”
Section: Discussion: Peptide Biosensors-advantages and Applicationsmentioning
confidence: 99%
“…54 Therefore, a large number of nanomaterials for biomolecule immobilization have been studied in recent years. [55][56][57] The unique properties of AuNPs provide a multifunctional platform for biomolecules. Cheng et al, 58 designed an AuNPs-assisted enzyme signal amplication method, which was used in paper enzyme-linked immunosorbent assay (ELISA) to detect PSA in human serum.…”
Section: Carrier Of Biomoleculesmentioning
confidence: 99%
“…25 Studies have shown that graphene and its derivatives exploited for tissue engineering scaffolds have the ability to promote the adhesion, proliferation and differentiation of stem cells. 26 Thus, graphene scaffolds that provide rigid surfaces can be combined with soft hydrogel scaffolds to obtain composite scaffolds for engineering the bone marrow niche.…”
Section: Introductionmentioning
confidence: 99%